Lexical Cohesive Devices in Narrative and Exposition Texts - Adnania Nugra Heni; Hermawati Syarif; Leni Marlina (English Language and Literature, 2018)
This study aims to find out the types of lexical cohesive devices found and prevailed in two different genres, in this case, narrative and exposition texts. This analysis will be based on theory of discourse connections proposed by Renkema. The objects of this research are six texts, three texts from narrative and three texts from exposition. This study is descriptive comparative with the presence of tables to show the comparison. The result shows that types of lexical cohesive devices which  prevailed in both of the genres were reiteration, especially repetition. Repetition is one of the most stable ways of pointing the same referent. It means that repetition tends to be used by the author of texts in creating a cohesive text since it is the type of lexical cohesive devices which mostly found in the texts. However, the type of repetition which prevailed in each genres were different. From that fact, it can be concluded that type of lexical cohesive devices presented in narrative and exposition texts depend on which genre they belong to.